Experiences in fosfomycin susceptibility testing and resistance mechanism determination inEscherichia colifrom urinary tract infections in the UK. Issue 2 (February 2019) - Cottell, Jennifer L.; Webber, Mark A.
Abstract : Purpose. : With an increase in the numbers of bacterial isolates resistant to first‐line antibiotics, there has been a revival in the use of older drugs including fosfomycin with novel mechanisms of action. We aimed to investigate the prevalence and genotypic nature of fosfomycin resistance in Escherichia coli from urinary tract infections (UTIs) using the various methods available in the clinical microbiology laboratory. Methodology. : In total, 1000 culture‐positive urine samples were assessed for the presence of E. coli and fosfomycin susceptibility was determined using the MAST Uri system, microbroth dilution, agar dilution and E‐test strips. Results/Key findings. : Initial investigation using breakpoint susceptibility testing on the MAST Uri system identified 62 of 657 (9.5 %) E. coli isolates as fosfomycin‐resistant (MIC≥32 μg ml −1 ). However, on further testing, a lower rate of eight of the 62 (1.3 %) were robustly confirmed to be resistant using microbroth dilution, agar dilution and E‐test strips. These true resistant isolates belonged to diverse E. coli multi‐locus sequence types and each had a unique set of chromosomal alterations in genes associated with fosfomycin resistance. Fosfomycin‐resistant isolates were not multiply drug resistant and did not carry plasmidic fosfomycin resistance genes. Therefore, the use of fosfomycin may be unlikely to drive selection of a particular clone or movement of transferrable resistance genes. Conclusion. : Fosfomycin remains a viable option for the treatment of E. coli in uncomplicated UTIs; different susceptibility testing platforms can give very different results regarding the prevalence of fosfomycin resistance, with false positives being a potential problem that may unnecessarily limit the use of this agent.